PHRASEOLOGISMS WITH ANTONYM COMPONENTS (Konferensiyalar | Conferences, 2024)
This article explores the phenomenon of antonyms, which exist in both phraseological and lexical units based on semantic relationships. Determining antonymy provides insight into the lexical meaning of phrases, aids in distinguishing meanings in polysemy, and helps define synonyms.